Animal breeding and feeding tools may close human nutrition gaps - Egelandsdal, Bjørg; Grabez-Ågren, Vladana; Mydland, Liv Torunn; Haug, Anna; Prestløkken, Egil (Frontiers in Animal Science, 2024)
The last century has witnessed many innovations in agriculture and food technologies that have ensured the production of sufficient quantities of good hygienic food. Animal scientists have contributed substantially to efficient breeding and feeding practices by adapting animals for faster growth and improving feed efficiency and utilization. Breeding goals and feeding recommendations have been proposed with a primary focus on profitability to promote significant changes in the macronutrient content, that is, animal body protein and fat reduction. However, improving the nutritional quality of meat was not included in the profit assessment. Increasing the lean meat fraction is consistent with the goal of public dietary guidelines for human nutrition proposed in 1980, emphasizing the importance of reducing the consumption of animal fat, particularly saturated fat. The application of breeding and feeding tools to modify and improve the fatty acid composition has been partly implemented in pigs and broiler chickens to supplement the dietary recommendations for humans. The health benefits of lean “red meat” have been questioned in recent years, with dietary guidelines and upper limits being introduced for human intake. Animal breeding indirectly reduces the total and heme iron (the redness generator) content in meat, owing to covariation with priority breeding goals. Two micronutrients play important roles in the human diet and are derived largely from meat (selenium) and milk (iodine) if the amount provided and absorbed is sufficient and predictable. The iodine content can be highly dependent on the use of novel (more sustainable) feeds. The micronutrients discussed in this study (Fe, Se, I, and vitamin D) highlight opportunities for the utilization of breeding and feeding knowledge to adjust their levels to procure meat with a high nutrient density. The gaps in micronutrient levels in humans must be addressed by navigating within approved animal feeding levels. Animal scientists must recognize the nutritional impact of breeding and feeding and advertise them. In addition, human nutritionists must acknowledge the existing and potential changes in animal production to meet the dietary guidelines. Sustainable food production within the “One Health Concept” can only be achieved through cooperation.